2016
DOI: 10.1038/sc.2016.122
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after acute traumatic spinal cord injury in Botswana: from admission to discharge

Abstract: Rehabilitation of patients with TSCI in Botswana has been going through big changes, and new rehabilitation objectives, such as techniques used for the management of bladder and bowel dysfunctions and the provision of technical aids, have been implemented, which likely can contribute to an overall improvement in the outcomes. However, basic care at the general wards is still lagging behind, causing high rates of pressure ulcers that significantly extend hospitalization periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
4
10
0
Order By: Relevance
“…In Nigeria, Nwankwo et al 20 reported neurologic improvement in 53% of patients undergoing surgery; however, they operated on only 1 ASIA A patient (6%) compared to 48% in our series. Similar to our results, Lofven et al 8 from Botswana reported an ASIA improvement rate of 16%. While a large study from Iran of 431 TSI patients reported early surgery (<48 hours) in 41% of patients, rates of neurologic improvement were unfortunately not included.…”
Section: Neurologic Outcomessupporting
confidence: 92%
See 2 more Smart Citations
“…In Nigeria, Nwankwo et al 20 reported neurologic improvement in 53% of patients undergoing surgery; however, they operated on only 1 ASIA A patient (6%) compared to 48% in our series. Similar to our results, Lofven et al 8 from Botswana reported an ASIA improvement rate of 16%. While a large study from Iran of 431 TSI patients reported early surgery (<48 hours) in 41% of patients, rates of neurologic improvement were unfortunately not included.…”
Section: Neurologic Outcomessupporting
confidence: 92%
“…The author(s) declared no potential conflicts of interest with respect to the research, authorship, and/or publication of this article. .303 21 24 .591 7 (6-12) 8 (7)(8)(9)(10)(11)(12)(13)(14) .193 33 40 .277…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Löfvenmark et al found that complete SCI was a strong dbidity, similarly Aarabi et al found that motor score of < 25 and ASIA A injury were strong predictors of morbidity which is also in keeping with the finding in this study. 6 32…”
Section: Discussionmentioning
confidence: 99%
“…Secondary injury to the traumatized cord is best prevented or minimized by adequate prehospital care, specialized acute treatment, and comprehensive rehabilitation facilitated by proper funding and health insurance. 6 7 8 Early access to specialized care after acute TSCI is associated with improved outcomes. 9 10 Patients who are admitted to specialist spinal care units within 24 hours of injury had fewer secondary complications.…”
Section: Introductionmentioning
confidence: 99%